THE MEDICINAL USE OF ENTOMOLOGICAL DRUGS USED BY TRIBAL COMMUNITIES OF EASTERN UTTAR PRADESH - KHAN, A.U.; SHARMA, V.P.; AZMI, H.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
Tribal communities use insects as drug to cure various viral, bacterial, clinical and physiological ailments viz. asthma, anaemia, abortion, bronchitis, delirium, exopthalmic goitre, filariasis, galactosaemia, impotancy, jaundice, leucorrhoea, rheumatism, tuberculosis prevalentin the eastern Uttar Pradesh, India.